“Evaluación de diferentes niveles de biofertilizantes en el rendimiento del cultivo de tomate (Lycopersicum esculentum Mill.) en la zona de Babahoyo” - Moreira Jiménez, Julio César (2018)
VIII. SUMMARY The present rehearsal was made in the lands of the Experimental Farm "San Pablo" of the Ability of Agricultural Sciences of the Technical University of Babahoyo, located in the km 7,5 of the road Babahoyo - Montalvo. The geographical coordinates are 010 47´49" of south latitude and 790 32´00" of longitude west and a height of 8 msnm. As siembra material it was used seeds of the variety "Marmande", distributed by the importadora Alaska. CORP. The treatments were studied with the help of products biofertilizantes Azototic + Fosfotic + Potasitic, in dose of 0,5 cm3 + 0,5 cm3 + 0,5 cm3/plant; 0,5 cm3 + 1 cm3 + 0,5 cm3/plant; 0,5 cm3 + 0,5 cm3 + 1 cm3; 1 cm3 + 0,5 cm3 + 0,5 cm3/plant; 1 cm3 + 1 cm3 + 1 cm3 and a treatment witness (chemical Fertilization), in dose of 6 g of N, 1,75 g of P, 4,5 g of K for plant whose dose of they applied at the 20 - 40 - 60 days after the transplant, while the Match and Potassium to the moment of the transplant and the Nitrogen to the 15-30 days after the transplant. The experimental design of Complete Blocks was used at random, with six treatments and four repetitions. The comparisons of the averages were made with the Test from Tukey to 95% of probability. For the results obtained in the investigation it was determined that the application of Azototic + Fosfotic + Potasitic, in dose of 0,5 cm3 + 0,5 cm3 + 0,5 cm3/plant, it influenced so that bigger plant height exists to the 30 and 60 days after the transplant; the treatment witness (conventional chemical Fertilization), with application of 6 g of N, 1,75 g of P, 4,5 g of K obtained bigger number of fruits for plant; regarding longitude and diameter of the fruit, the employment of Azototic + Fosfotic + Potasitic, in dose of 0,5 cm3 + 0,5 cm3 + 0,5 cm3/plant reached better averages; the weight of the fruit reported bigger average in the treatment witness (conventional chemical Fertilization), with application of 6 g of N, 1,75 g of P, 4,5 g of K for plant. In the yield during the first one, second and third crop, the witness generated better averages, as well as bigger net profit. Keywords: biofertilizers, tomato, azototic, fosfotic, potasitic.